Axonal mRNA binding of hnRNP A/B is crucial for axon targeting and maturation of olfactory sensory neurons - Nanaho Fukuda; Tomoyuki Fukuda; Piergiorgio Percipalle; Kanako Oda; Nobuyuki Takei; Kevin Czaplinski; Kazushige Touhara; Yoshihiro Yoshihara; Toshikuni Sasaoka (Cell Reports, 2023)
Summary: Spatiotemporal control of gene expression is important for neural development and function. Here, we show that heterogeneous nuclear ribonucleoprotein (hnRNP) A/B is highly expressed in developing olfactory sensory neurons (OSNs), and its knockout results in reduction in mature OSNs and aberrant targeting of OSN axons to the olfactory bulb. RNA immunoprecipitation analysis reveals that hnRNP A/B binds to a group of mRNAs that are highly related to axon projections and synapse assembly. Approximately 11% of the identified hnRNP A/B targets, including Pcdha and Ncam2, encode cell adhesion molecules. In Hnrnpab knockout mice, PCDHA and NCAM2 levels are significantly reduced at the axon terminals of OSNs. Furthermore, deletion of the hnRNP A/B-recognition motif in the 3′ UTR of Pcdha leads to impaired PCDHA expression at the OSN axon terminals. Therefore, we propose that hnRNP A/B facilitates OSN maturation and axon projection by regulating the local expression of its target genes at axon terminals.